Recreational forest experience: a case of mount Kinabalu climbing activity, Sabah Malaysia - Hamimah Talib; Roszehan Mohd Idrus; Chan, Jennifer Kim Lian (Impact Journals, 2015)
The use of tropical forest parks as recreation resource is receiving increasing response from the public. Although its contribution as a recreational resource is apparent, more in-depth information on how it relates to and benefits the users are still unclear. The purpose of this study is to understand the recreation experience and satisfaction of visitors in a tropical forest park setting with the use of mixed method approach (quantitative and qualitative techniques). Three hundred and seven questionnaire surveys and twenty-two interviews were conducted with purposively sampled climbers of Mount Kinabalu in Kinabalu Park, Sabah, Malaysia. The Recreation Experience Preference (REP) scale was used to elicit visitors’ experience types gained through participation, and in-depth interview analysis based on Motivation-Hygiene Theory was conducted to understand their experience. This study found seven dimensions of recreation experiences that ranged from “Achievement-Stimulation” (highest mean score) to “Security-Comfort zone” (lowest mean score), which indicate visitors’ psychological needs fulfilled from participation. This study contributes to the understanding of visitors’ recreational experience in the specific site and activity, which highlights the values and importance of this resource. Recommendations for park management and avenues for future studies were identified and discussed.